GRATITUDE JOURNAL UNTUK MENINGKATKAN RESILIENSI SANTRI DALAM MENGHADAPI PANDEMI COVID-19: SEBUAH KERANGKA KONSEPTUAL [GRATITUTE JOURNAL TO IMPROVE SANTRI RESILIENCE IN FACING THE COVID-19 PANDEMIC: A CONCEPTUAL FRAMEWORK] - Nurmalasari, Ela; Sanyata, Sigit (Acta Islamica Counsenesia: Counselling Research and Applications, 2021)
Since the enactment of the large-scale repatriation of students at several Islamic boarding schools, followed by PSBB, regional quarantine, to the new normal, it cannot be denied that students and Islamic boarding schools have become an integral part affected by the COVID-19 pandemic. The process of good adaptation in responding to challenges with the strength of determination and adversity in the context of psychology is called resilience. This study aims to determine the use of a gratitude journal to increase student resilience in the face of the COVID-19 pandemic. The research method used is literature study. The findings of this study are as a form of expression or a form of gratitude, students in Islamic boarding schools are already accustomed to expressing in the form of prayer. Few are aware of the importance of expressing gratitude appropriately and consistently. Making a gratitude journal can be an effective medium for expressing gratitude every day. Also as material for reflection and evaluation to be better tomorrow. Counselors at Islamic boarding schools can use a gratitude journal in providing guidance and counseling services, both in individual and group settings.